Functional gait assessment in patients with relapsing-remitting Multiple Sclerosis and relation to the risk of falls. - Moraes, Bruno; Orsini, Marco; Fiorelli, Rossano; Marinho, Victor; Teixeira, Silmar; Bastos, Victor Hugo; Matta, André (Fisioterapia Brasil, 2018)
Objective: To demonstrate correlation functional evaluations of gait on the patients with Multiple sclerosis, using a noninvasive method by means of Timed Up and Go, Tinetti test, 25-Foot Walk test and Expanded Disability Status Scale (EDSS). Methods: We evaluated 40 patients with Multiple sclerosis using Timed Up and Go, Tinetti test, 25-Foot Walk test and EDSS scale. Results: In present study, we have observed moderate to high correlations between EDSS and Timed Up and Go, Tinetti test and 25-Foot Walk test (p<0.0001). The patients reported longer execution times for Timed Up and Go and 25-Foot Walk tests and lower scores on the Tinetti test. We found a direct correlation between illness duration, EDSS scale, Timed Up and Go execution time, 25-Foot Walk execution time and Tinetti test score (p<0.0001). Conclusion: Proper gait and fall risk evaluations are important in order to avoid complications that are related to Multiple sclerosis.